Messages from the ‘Older Brother’: Djawa Baroe Magazine and the Japanese Propaganda in Indonesia in 1943-1945 - Putut Widjanarko (Ikatan Sarjana Komunikasi Indonesia, 2020)
The Japanese occupation of East Asia during World War II was accompanied by its propaganda targeting the local population. In Indonesia, the military government, among other things, published Djawa Baroe, a fortnightly magazine published from January 1, 1943, to August 1, 1945. Compared to other magazines, this bilingual magazine (in Japanese and Bahasa Indonesia) Djawa Baroe was unique: it featured ample photographs and illustrations. Qualitative content analysis method enables this study to find the meaning of a theme in its holistic political, social, and cultural contexts beyond the number of its occurrences in the text offered by quantitative content analysis. All the issues of Djawa Baroe are examined in detail and reiteratively. Six themes can be found in Djawa Baroe, i.e., the friendship between Japanese and Indonesians, the description of Japanese military prowess, the exaltation of nationalism, and the preparation for the war, the evil nature of Western power, the role of women in society, and entertainment. The study concludes that along with the development of the Pacific War that turned against the Japanese, Djawa Baroe moved its emphasis on long-range goals at the high psychological level to influence and win the hearts and minds of Indonesian people, to a more immediate result and practical guide in facing the imminent war. On the other hand, against the original intention of the Japanese propaganda, Djawa Baroe may have helped its educated readers to imagine their future nation-state, Indonesia.